Species composition and abundance of mangrove gastropods in Desa Sutera, Kayong Utara, West Kalimantan - Safitri, Ikha; Ayzah, Dzul Khoidzah All; Nurdiansyah, Syarif Irwan; Nguyen, Duc-Hung (Universitas Islam Negeri Sumatera Utara, 2024)
The mangrove ecosystem in Desa Sutera, Kayong Utara Regency, West Kalimantan, Indonesia, serves as a habitat for various species of gastropods, many of which hold significant ecological and economic value. Data collection on gastropod species in this region is vital for establishing a baseline understanding of coastal and marine biodiversity, which is essential for the development of integrated and sustainable coastal management strategies. This study aimed to assess the species composition and abundance of mangrove gastropods in Desa Sutera. Sampling was conducted in May 2024 during low tide across four stations using quadrat transects. Thirteen species of mangrove gastropods were identified, representing nine genera and seven families, including Chicoreus capucinus, Clypeomorus bifasciata, Cassidula nucleus, Littoraria carinifera, L. melanostoma, L. scabra, Onchidium sp., Nerita balteata, Neripteron violaceum, Pirenella alata, P. cingulata, Cerithidea quoyii, and C. obtusa. Among these, P. cingulata and L. carinifera were the most abundant, whereas L. melanostoma and C. obtusa were the least prevalent. The gastropods were found inhabiting sandy and rocky substrates, as well as attached to the roots, trunks, and leaves of mangrove trees. This finding offers essential insights into the biodiversity and community structure of mangrove gastropods in the region, forming a basis for conservation and management strategies to protect this vital ecosystem.